Association between non-alcoholic hepatic steatosis and hyper reactive blood pressure response on the exercise treadmill test. Issue 8 (19th January 2016) - Laurinavicius, A.G.; Bittencourt, M.S.; Blaha, M.J.; Nary, F.C.; Kashiwagi, N.M.; Conceiçao, R.D.; Meneghelo, R.S.; Prado, R.R.; Carvalho, J.A.M.; Nasir, K.; Blumenthal, R.S.; Santos, R.D.
Abstract : Aims: Non-alcoholic hepatic steatosis (HS) is associated with hypertension and increased cardiovascular risk. While Blood pressure hyper-reactive response (HRR) during peak exercise indicates an increased risk of incident hypertension and increased cardiovascular risk, no data on the association of non-alcoholic HS and HRR exists. In this study, we have evaluated the association of HS with HRR. Methods: We included 13 410 consecutive individuals with a mean age: 42.4  ±  8.9 years, 3561 (26.6%) female with normal resting blood pressure and without a previous diagnosis of hypertension, who underwent symptom limited exercise treadmill test, abdominal ultrasonography and clinical and laboratory evaluation. HS was detected by abdominal ultrasonography. HRR was defined by a peak exercise systolic blood pressure  >220 mmHg and/or elevation of 15 mmHg or more in diastolic blood pressure from rest to peak exercise. Results: The prevalence of HS was 29.5% ( n   =  3956). Overall, 4.6% ( n  =  619) of the study population presented a HRR. Subjects with HS had a higher prevalence of HRR (8.1 vs. 3.1%, odds ratio 2.8, 95% CI 2.4—3.3, P  <  0.001). After adjustment for body mass index, waist circumference, fasting plasma glucose and low density lipoprotein cholesterol, HS (odds ratio 1.4, 95% CI 1.1–1.6, P  =  0.002) remained independently associated with HRR. HS was additive to obesity markers in predicting exercise HRR. Conclusions: Non-alcoholic HS is independently associated with hyper-reactive exercise blood pressure response.